Answer:
Equation (1) should be multiplied by (9/4) to eliminates the variable x by addition.
Explanation:
Here, the given system of equation is:
24 x + 3 y = 72
- 18 x + y = 30
Now, equation (2) x 3 = - 18(3) x + (3) y =(3) 30
⇒ -54 x + 3 y = 90
So, the x term = -54 x
Now, for x to be eliminated in the first term,
24 x should be transformed in to + 54 x as 54 x - 54 x = 0
Let us assume, 24x is multiplied by a factor m so that
24x (m) = 54 x
⇒
![m = (54x)/(24x) = (9)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5cnpd0uh3ooegoqu2nsaz0497ukijs5nky.png)
or, m = 9/4
Hence, equation (1) should be multiplied by (9/4) to eliminates the variable x by addition.